Mathematics and Numeracy Policy - Jamaica. Ministry of Education, Youth and Culture (Ministry of Education, Youth and Culture, 2003)
Informed by reviews of research and by international trends in mathematical education, the Jamaican Ministry of Education has adopted a policy position that places emphasis on numeracy as a proficiency to be attained by all students in the educational system. Within this policy emphasis is placed on the numeracy strategy aimed at promoting effective teaching approaches at both primary and secondary levels.
Keywords: Educational policies